Zinc-oxide and nano ZnO oxide effects on growth, some biochemical aspects, yield quantity, and quality of flax (Linum uitatissimum L.) in absence and presence of compost under sandy soil - Sadak, Mervat Shamoon (2021)
The obtained results showed that adding of compost to the sandy soil by 3.0 ton/fed, increased markedly growth parameters (shoot and root length (cm), fresh and dry weights (g), photosynthetic pigments (chlorophyll a, chlorophyll b, carotenoids, and total pigments (μg/g fresh wt)), free amino acids and proline (mg/100 g dry wt), total carbohydrate percentage, yield quantity and quality (technical shoot, fruiting zone lengths and plant height (cm), No. of fruiting branches/plant and No. of capsules/plant, weight of straw (g), weight of 1000 seeds (g), biological yield (kg/fed), seed yield (kg/fed), and straw yield (kg/fed)), oil percentage, and oil yield (kg/fed) compared to control treatments (without compost). Also, the obtained data clarified that applied foliar treatment with normal ZnO with rates 40 mg/L significantly increased the yield and all parameters of flax plant during studied growing seasons. The interaction between compost addition and different concentrations of either ZnO or nano ZnO revealed that different concentrations increased different studied parameters without or with the addition of compost to sandy soil as compared with untreated plants.